Workplace stress [ - Weber Charles M. (SafetyMax Corp. Pte Ltd, 1994)
This program teaches the employee to recognize workplace situations that cause stress, recognize symptoms of stress, and differentiate between positive and negative stress. Simple stress relief techniques and exercises are illustrated